Cervical radiculopathy caused by vertebral artery loop formation: a case report - Tack, Laura (Radiol Case Rep, 2021)
Vertebral artery loop formation is a rare cause of cervical radiculopathy. We report a case of a 70-year-old man who was referred because of a chronic cervicobrachialgia. Initial plain cervical x-ray showed widening of the left C3-C4 intervertebral foramen. Additional magnetic resonance angiography revealed the presence of a vertebral artery loop, which had migrated into the left C3-C4 neural foramen and caused compression of the left C4 nerve root. Surgery was considered, but the patient’s symptoms resolved with conservative treatment. The aim of this case report is to raise the knowledge of both clinicians and radiologists about vertebral artery loop formation as a rare but potentially life-threatening cause of cervical radiculopathy. If overlooked, cerebrovascular stroke during transforaminal cervical steroid injections or catastrophic vertebral artery damage during surgery may occur.